Literature Review: Analisis Senyawa Aktif Ekstrak Dan Fraksi Tanaman Berpotensi Sebagai Antiplatelet - Virena Audelia Rambang; Fatma Ria; Natalia Sri Martani (Herb-Medicine Journal: Terbitan Berkala Ilmiah Herbal, Kedokteran dan Kesehatan, 2021)
ABSTRACT Stroke is still the main cause of morbidity and mortality in the world. Research found "aspirin resistant" in 5-60% of cases, it’s necessary to develop researches related to antiplatelet therapy. In the antiplatelet research on plant extracts, some were significant and some weren’t. To determine active compound of plant extracts, fractions, mechanism of action, extraction method, isolation methods of active compounds with antiplatelet activity. Literature studies with a systematic approach, data from original articles in GoogleScholar, PubMed. Obtained 32 literatures through data quality analysis and topic suitability. Data synthesis using PICO method. 30 journals significantly have antiplatelet activity, 2 weren’t, the most found compounds were flavonoids, quercetin. Mechanism of action as an antiplatelet, antithrombotic. Extraction methods maceration, reflux, juice, sonication, soxhlet, distillation. The isolation methods using CC, HPLC, TLC, NMR. Conclusion: Insignificant results are from AGE and raw, boiled, fried garlic, both tested in vivo. Journals that significantly have antiplatelet results are from extracts of strawberries, grape seeds, Allium sp., Bay leaves, mango peel, tomatoes, Hawthorn, C.aromatica Salisb., Red ginger, G.verrucosa, S.polycystum, olive leaves, M.alba, P.baumii, R.vernicflua, A.shikokiana, katuk leaves, tempuyung leaves, red cabbage, M.obovata, lempeni leaves, kajajahi leaves, starfruit leaves, U.macrocarpa, M.citrifolia, C.limon, L.japonica, E.bicyclis, S.deserta, V.labrusca. Most found active compound with antiplatelet activity are flavonoids, fraction quercetin. Mechanism of action on COX-1, AA, TXA2, P13K pathways, increased cAMP, VASP stimulation. Extraction methods by maceration, reflux, soxhlet, sonication, juice, distillation. Isolation methods using CC, HPLC, TLC, NMR